The Influence of Electronic Word of Mouth, Social Media, and Lifestyle on Purchasing Decisions on Gembong Gedhe’s Bread in Surakarta City - Shuwaifi, Ahmad; suswadi; Prasetyo, Agung (Agribusiness Department, Agriculture Faculty, Tunas Pembangunan University, Surakarta, Indonesia, 2024)
Many things can influence consumers before making a purchase at the kingpin bakery Gedhe , including electronic word of mouth, social media, and lifestyle. Study This aims to determine the influence of electronic word of mouth and media social, and lifestyle on purchasing decisions at the Roti Gembong Gedhe shop by students in Surakarta City. The research method is descriptive and analytical. Data used data primary and secondary data. The research sample is 100 respondents with a population students in Surakarta City. The analytical method used is analysis multiple linear regression. The research results show the characteristics of the most respondents is a woman amounting to 64% , with the majority of income amounting to not enough from IDR 1,500,000 per month . The majority of respondents made purchases at the Gembong Gedhe bakery 1 time by 32% and There are 15% who actively follow Roti Gembong Gedhe's Instagram . A total of 91% of respondents are also actively involved in reading reviews and comments online with an intensity of 1-3 times a day. Results of multiple linear regression analysis shows that the three independent variables are electronic word of mouth, social media and lifestyle together have a very real influence on purchasing decisions at the Gembong Gedhe Bakery partially there are 2 independent variables that have a very real influence on purchasing decisions at the Gembong Gedhe bakery that are Social media variables (x2) and Lifestyle variables (x3) . The suggestion from this research is that Roti Gembong Gedhe prioritizes it’s social media , so you can develop the Gembong Gedhe bread account from various platforms in line with societal trends . Gembong Gedhe bakery can also develop customized products with the lifestyle of consumers which targeted by the Gembong Gedhe bakery . It is hoped that further research can expand the area research and expanding research objects